Key Morphological Events following Late-Season Goosegrass (Eleusine indica) Germination. (21st November 2018) - Kerr, Robert Andrew; McCarty, Lambert B.; Bridges, William C.; Cutulle, Matthew
Abstract: Goosegrass is a weedy C4 species throughout the world and a major pest in turfgrass systems. Further research is needed to characterize morphological events of goosegrass germinating in late summer to enhance long-term management programs. The objective of this study was to determine whether goosegrass germinating on August 15 will complete a life cycle before the first killing frost, typically November 15 in Clemson, SC. A biotype from Clemson, SC, was collected and a growth-chamber experiment was conducted to simulate autumn maximum and minimum temperatures. Culm, leaf, root, and raceme biomass measurements were recorded weekly, and growth curves were modeled. The inflection point (i.e., point of maximum growth) occurred for the following growth parameters: culm dry weight at 26.5 d after emergence (DAE), leaf dry weight at 26.6 DAE, number of racemes per plant at 50.7 DAE, raceme dry weight (including germinable seed) at 56.0 DAE, and root dry weight at 42.1 DAE. The completion of the life cycle occurred on October 22 (68 DAE), approximately 3 wk before the typical first killing frost in Clemson, SC. In summary, turf managers need to address goosegrass that germinates through approximately the first week of September at this location to avoid production of viable seed.